2018
DOI: 10.1007/s12182-018-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of performance and emission characteristics of waste cooking oil as biodiesel in a diesel engine

Abstract: Biodiesel is one of the most popular prospective alternative fuels and can be obtained from a variety of sources. Waste frying oil is one such source along with the various raw vegetable oils. However, some specific technical treatments are required to improve certain fuel properties such as viscosity and calorific value of the biodiesel being obtained from waste cooking oil methyl ester (WCOME). Various treatments are applied depending on the source and therefore the composition of the cooking oil. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…These results were compared to ASTM standard. Result obtained shows that the properties of biodiesel produced fell within the acceptable range, which is also in agreement with the work of [22,23]…”
Section: Physicochemical Properties Of the Famesupporting
confidence: 90%
“…These results were compared to ASTM standard. Result obtained shows that the properties of biodiesel produced fell within the acceptable range, which is also in agreement with the work of [22,23]…”
Section: Physicochemical Properties Of the Famesupporting
confidence: 90%
“…However, it has to be concluded that various factors affects the NO and NOx formation which may result in contradictory readings. The ambient conditions, gas residence time of the fuels, fuel spray characteristics, EGR application, oxygen content, physical condition of the experimental equipment, and fluctuations can all affect the NO and NOx formation of any fuel, hence it is difficult to figure out the most dominant parameter causing the difference [43,[64][65][66].…”
Section: Injection and Combustion Characteristicsmentioning
confidence: 99%
“…It has similar emission characteristics to other types of biodiesel. The WCO biodiesel burns with lower temperatures, thus resulting in lower NOX emission [9][10][11][12]. However, in some other studies, NOX increases and soot emissions decrease compared to the known high NOX profile of biodiesel [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%